The quadratic isoperimetric inequality for mapping tori of free group automorphisms - Bridson, M; Groves, D (2008)
If F is a finitely generated free group and φ is an automorphism of F then F \rtimes_φ Z satisfties a quadratic isoperimetric inequality.